Produção de sedimentos em suspensão em uma microbacia hidrográfica urbana - Santos, André Tiago dos (2017)
Considering the problem of sediment dynamics in urban areas and the lack of information on the quantitative aspects of sediment yield in urban areas, this study aimed to evaluate the possibility of applying the traditional MUSLE model adjusted to the Guamirim river watershed in the urban area of São Miguel do Oeste – SC. Classical monitoring techniques were used to quantify the concentration of suspended sediments (sampling by the same width increase) during rainfall events from May to October 2016. At the same time, with the help of a Geographic Information System (GIS) platform, the numerical model of the terrain and the orthophoto of the São Miguel do Oeste - SC town were used to define the relief features and the use and occupation of urban land. In order to verify the observed and calculated values, two statistical analyses were used: coefficient of efficiency of the model (COE) and mean square error (MSE). The sediment yields observed in the field during twelve rainfall events distributed throughout the year 2016 were calculated. The results were compared with the sediment yields estimated by the traditional MUSLE (empirical coefficient used) and the MUSLE adjusted for the urban watershed under study. The values obtained by traditional MUSLE underestimated the events while the adjusted MUSLE superestimated the observed productions. The statistical analysis showed little variability between what was observed and the values obtained by the adjusted MUSLE. It can be concluded that it can be used in the urban area of São Miguel do Oeste SC, as long as the other parameters of the model do not change (land use and occupation).